Time and Energy Minimized Trajectories for LANs of Drones - Sandaruvan Rajasinghege; Rohan de Silva (International Journal of Engineering and Management Research, 2019)
Controlling UAV movements in a UAV network is a critical but not well-studied research area in UAV network research. In this paper, we consider the problem of finding time and energy minimized trajectories for LANs of Drones (LoDs) by computationally inexpensive method. A LoD is a novel type of UAV network, which uses a minimum number of UAVs to perform any collaborative task. For both criterions of time and energy minimization, we formulate separate nonlinear constrained optimization problems and use Sequential Quadratic Programming method to obtain local optimum solutions. These minimization methods were tested by carrying out a range of simulations in MATLAB environment.